2018
DOI: 10.1177/2049463718820056
|View full text |Cite
|
Sign up to set email alerts
|

The context of litigation in evaluating physical and psychological outcomes from pain management programmes

Abstract: Objectives: There has been extensive research in evaluating chronic pain in the context of litigation while considering the implications that it can have on healthcare outcomes and rehabilitation progress. The aim of this article is to present retrospective observational data about the levels of disability and distress reported by patients with ongoing litigation at the start and following a UK-based multidisciplinary pain management programme (PMP) when compared with those without litigation. Method: Between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 21 publications
(26 reference statements)
3
3
1
Order By: Relevance
“…Our analyses support and strengthen these findings. Unlike past studies that found psychological factors to partially (Giummarra et al, 2017a; Grant et al, 2014; O'Donnell et al, 2015; Twiddy et al, 2018) or fully (Giummarra et al, 2017b) mediate long-term psychological and recovery outcomes in compensation groups, our analyses indicate that long-term psychological distress associated with compensation is better explained by the concurrent level of functioning and disability. In other words, it is the injury-related disability and vulnerability that best explains any detrimental effect to psychological health, and not the compensation process itself.…”
Section: Discussioncontrasting
confidence: 95%
See 4 more Smart Citations
“…Our analyses support and strengthen these findings. Unlike past studies that found psychological factors to partially (Giummarra et al, 2017a; Grant et al, 2014; O'Donnell et al, 2015; Twiddy et al, 2018) or fully (Giummarra et al, 2017b) mediate long-term psychological and recovery outcomes in compensation groups, our analyses indicate that long-term psychological distress associated with compensation is better explained by the concurrent level of functioning and disability. In other words, it is the injury-related disability and vulnerability that best explains any detrimental effect to psychological health, and not the compensation process itself.…”
Section: Discussioncontrasting
confidence: 95%
“…Similar to our findings, most studies consistently found poorer health, mainly psychological health, in compensation groups at all time points (Elbers et al, 2013; Murgatroyd et al, 2016; Twiddy et al, 2018), while some recovery does occur over time (Elbers et al, 2013; Murgatroyd et al, 2016; Twiddy et al, 2018). Rates of recovery, however, varied across studies, being lower (Elbers et al, 2013), or similar to non-compensation groups (Twiddy et al, 2018). These inconsistencies could reflect selection biases, that is, differences in pre-injury and injury characteristics and other sources of heterogeneity (Elbers et al, 2013; Spearing et al, 2012b; Twiddy et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations